Riboflavin Is Directly Involved in N‐Dealkylation Catalyzed by Bacterial Cytochrome P450 Monooxygenases. (30th April 2020) - Zhang, Chengchang; Lu, Meiling; Lin, Lin; Huang, Zhangjian; Zhang, Rongguang; Wu, Xuri; Chen, Yijun
Abstract: Like a vast number of enzymes in nature, bacterial cytochrome P450 monooxygenases require an activated form of flavin as a cofactor for catalytic activity. Riboflavin is the precursor of FAD and FMN that serves as indispensable cofactor for flavoenzymes. In contrast to previous notions, herein we describe the identification of an electron‐transfer process that is directly mediated by riboflavin for N‐dealkylation by bacterial P450 monooxygenases. The electron relay from NADPH to riboflavin and then via activated oxygen to heme was proposed based on a combination of X‐ray crystallography, molecular modeling and molecular dynamics simulation, site‐directed mutagenesis and biochemical analysis of representative bacterial P450 monooxygenases. This study provides new insights into the electron transfer mechanism in bacterial P450 enzyme catalysis and likely in yeasts, fungi, plants and mammals. Abstract : Direct transfer : Riboflavin directly transfers electrons to bacterial cytochrome P450 monooxygenases in an oxidative N‐dealkylation. A new mechanism for the electron‐transfer process is proposed that could be generally applicable to numerous P450‐like monooxygenases that lack the reductase domain.